2021
DOI: 10.1016/j.nmni.2021.100910
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial coinfection among coronavirus disease 2019 patient groups: an updated systematic review and meta-analysis

Abstract: Background The pandemic of SARS COV-2 raised the attention toward bacterial coinfection and their role in COVID-19 disease. This study aims to systematically review and identify the pooled prevalence of the bacterial coinfection in the related articles. Methods A comprehensive search was conducted in international databases, including Medline, Scopus, Web of Science, and Embase, to identify the articles on the prevalence of Bacterial coinfections in COIVD-19 patients fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
1
17
1
1
Order By: Relevance
“…"Metaprop" commands were applied in a forest plot to estimate the pooled prevalence with a 95% confidence interval (CI). A random-effects model was used to estimate the pooled prevalence [15][16][17][18][19][20]. Meta-regression analysis was used to evaluate the effect of the WHO region, sample size, and age on heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…"Metaprop" commands were applied in a forest plot to estimate the pooled prevalence with a 95% confidence interval (CI). A random-effects model was used to estimate the pooled prevalence [15][16][17][18][19][20]. Meta-regression analysis was used to evaluate the effect of the WHO region, sample size, and age on heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis study showed 8.1% of coinfection among critically ill patients compared to 5.9% hospitalized ones. 85 Soltani et al 86 showed the prevalence of 20.97 bacterial co‐infection in COVID‐19‐infected cases. Another important aspect of bacterial co‐infection prevalence is about empirical bacterial treatment (52).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with BC had higher illness severity scores compared with those without BC, measured by APACHE II (14)(15)(16)(17)(18) versus 13 [IQR 10-17], p = 0.001) and SOFA score (5)(6)(7)(8) versus 4 [IQR 3-7], p < 0.001). Subjects with BC had higher incidence of hypertension (54.7% versus 45.6%, p = 0.003), diabetes (30.2% versus 22.6%, p = 0.002), chronic obstructive pulmonary disease (10.9% versus 7.4%, p = 0.02) and hematological disease (5.4% versus 3.1%).…”
Section: Comparison Of Bacterial Co-infection and Non-co-infection Gr...mentioning
confidence: 99%